Systematic study of (p, n) and (p, 2n) reactions on 110Cd. (July 2023) - Vashi, Vibhuti; Makwana, Rajnikant; Quintana, B.; Mehta, M.H.; Singh, R.K.; Soni, B.K.; Chauhan, R.; Mukherjee, S.; Abhangi, M.; Vala, S.; Singh, N.L.; Patel, G.B.; et al.
Abstract: Standard activation analysis technique with γ ray spectroscopy via off-line mode was utilized for reaction cross section estimation. The proton beam was transported from the BARC-TIFR accelerator and targeted on the n a t Cd target. The 16 MeV proton beam irradiated the sample, and Copper foil was utilized as an energy degrader. The activation cross sections were estimated for 110 Cd(p, n) reaction for the ground state (J π = 7 + ) population of 110 In nucleus and 110 Cd(p, 2n) 109 In reaction at 14.14 MeV of proton energy. Along with experimental measurements, the theoretical study has been carried out for ground and metastable states population by utilizing the nuclear model code TALYS-1.95, EMPIRE-3.2.3, and ALICE-2014 for both reaction channels. The estimated cross sections are valuable for the improvement of theoretical nuclear model codes for a comprehensive knowledge of nuclear reaction mechanisms. The produced isotopes 109, 110 In have significant importance in Positron Emission Tomography (PET) studies. The present study is a dive into the phenomenological and microscopic level density models of different nuclear model codes in predicting excitation functions. Highlights: Standard activation analysis technique was utilized for data analysis. Cross sections were measured for (p, n) and (p, 2n) reactions on 110 Cd. Cd is important for nuclear reactors and medicines-based applications. Ground to metastable state cross section ratio was calculated for 110 Cd(p, n) 110 In. Phenomenological and microscopic-level density models used for data prediction.